Modelling the impact of compliance with dietary recommendations on cancer and cardiovascular disease mortality in Canada - Bélanger, M; Poirier, M; Jbilou, J; Scarborough, P (Elsevier, 2014)
Objectives: Despite strong evidence indicating that unbalanced diets relate to chronic diseases and mortality, most adults do not comply with dietary recommendations. To help determine which recommendations could yield the most benefits, the number of deaths attributable to cardiovascular diseases and cancer that could be delayed or averted in Canada if adults changed their diet to adhere to recommendations were estimated. Study design: Macrosimulation based on national population-based survey and vital statistics data. Methods: A macrosimulation model was used to draw age- and sex-specific changes in relative risks based on the results of meta-analyses of relationship between food components and risk of cardiovascular disease and diet-related cancers. Inputs in the model included Canadian recommendations (fruit and vegetable, fibre, salt, and total-, monounsaturated-, polyunsaturated-, saturated-, and trans-fats), average dietary intake (from 35107 participants with 24-h recall), and mortality from specific causes (from Canadian Vital Statistics). Monte Carlo analyses were used to compute 95% credible intervals (CI). Results: The estimates of this study suggest that 30540 deaths (95% CI: 24953, 34989) per year could be averted or delayed if Canadians adhered to their dietary recommendations. By itself, the recommendation for fruit and vegetable intake could save as many as 72% (55-87%) of these deaths. It is followed by recommendations for fibres (29%, 13-43%) and salt (10%, 9-12%). Conclusions: A considerable number of lives could be saved if Canadians adhered to the national dietary intake recommendations. Given the scarce resources available to promote guideline adhesion, priority should be given to recommendations for fruit and vegetable intake. © 2013 The Royal Society for Public Health.